2008
DOI: 10.1016/j.micpath.2008.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a gene for a fibronectin-binding protein of the oral bacterium Streptococcus mutans partially impairs its adherence to fibronectin

Abstract: A sequence of 1,647 base pairs in length of S. mutans DNA that encodes for a 63 kDa protein with significant amino acid similarity with fibronectin-binding proteins of S. pyogenes and S. gordonii was cloned. The putative recombinant fibronectin-binding protein of S. mutans was purified using affinity chromatography and the cloned protein was used to prepare polyclonal antibodies against the recombinant protein. In immunoblot assays, antibodies against the S. pyogenes fibronectinbinding protein, FBP54, were cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Moreover, continuous detections of this bacterium in specimens from patients suffering from such disease emphasize the importance of S. mutans in IE (Gauduchon et al, 2001;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Indeed, studies to clarify specific components involved in IE in S. mutans have also been performed worldwide (Beg et al, 2002;Jung et al, 2009; MatsumotoNakano et al, 2009;Miller-Torbert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, continuous detections of this bacterium in specimens from patients suffering from such disease emphasize the importance of S. mutans in IE (Gauduchon et al, 2001;Nomura et al, 2006;Vose et al, 1987;Ullman et al, 1988). Indeed, studies to clarify specific components involved in IE in S. mutans have also been performed worldwide (Beg et al, 2002;Jung et al, 2009; MatsumotoNakano et al, 2009;Miller-Torbert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On: Fri, 11 May 2018 21:36:29 involved in IE in S. mutans have also been performed worldwide (Beg et al, 2002;Jung et al, 2009;MatsumotoNakano et al, 2009;Miller-Torbert et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PavA homologues have been identified in other streptococci; these include Streptococcus gordonii FbpA (20), Streptococcus pyogenes FBP54 (21,22), and Streptococcus mutans SmFnB (23). A similar report showed that SfbA, a PavA homologue of group B streptococci, is important in the interaction of these bacteria with the blood-brain barrier endothelium and in the pathogenesis of neonatal meningitis (24).…”
mentioning
confidence: 97%
“…Similar to the pneumococcal adherence and virulence factor A (PavA) of Streptococcus pneumoniae, EfbA displays an unconventional structure for adhesins in that it lacks an N-terminal signal sequence for targeting the protein to the Sec system and a C-terminal LPXTG cell wall anchorage motif (14-16). Homologous proteins lacking these motifs include Fbp54 of Streptococcus pyogenes (17), FbpA of Streptococcus gordonii (18), the Streptococcus mutants SmFnB (19), and the group B streptococcus SfbA (20), collectively referred to as PavA-like proteins, several of which were shown to be involved in bacterial adherence to fibronectin and/or to mediate virulence in experimental models (15)(16)(17)(18)(19)(20)(21).E. faecalis JH2-2 EfbA consists of an N-terminal predicted domain involved in fibronectin binding (FbpA; amino acids 4 to 429), followed by a domain of unknown function (Duf814; amino acids 448 to 533) often observed in association with FbpA.…”
mentioning
confidence: 99%